HIGH-PRECISION U-PB ZIRCON GEOCHRONOLOGY AND THE STRATIGRAPHIC RECORD - Bowring S.A.; Schmitz M.D. (My University, 2003)
The rock stratigraphic record exists as a rich, albeit complex and incomplete repository of Earth history, tracing the processes of biological evolution, climate change, oceanic and atmo-spheric chemistry, sea-level fluctuations, mountain-building and erosion, and basin subsidence. Without a detailed and precise temporal framework, however, the richness of the record, including global stratigraphic correlations, evaluation of cyclicity and rates of regional and global change, major sedimentary depositional hiatuses, and biological extinctions cannot be fully exploited.